(untitled) (Terr@ Plural, 2022)
Investigating the concept of landscape through its representation is a multidisciplinary theme that can reveal much of the human trajectory and how it relates to, perceives, and interferes with its surroundings. The investigation proposed here aims to point out possibilities of analysis from the selection of some pieces of art, and paintings, in which the landscape is represented, either as a background, either as the main theme or in dialogue with the other elements. The way it appears highlighted, its colors, compositional relationships, and other elements are fundamental to understanding how the category of landscape would perceive, understood, and represented. In the end, it is possible to understand it as part of a text not only in what could be readily seen but beyond it. For this, the images were from Panosfsky’s Iconography and Iconology, extrapolating it also in the light of Cassirer, supported by Cosgrove’s geographical reflections, especially in his book ‘Palladian Landscape’.